Multifunctional Anti-Alzheimer’s Disease Effects of Natural Xanthone Derivatives: A Primary Structure-Activity Evaluation - Hu, Xiaoyu; Liu, Chan; Wang, Kaichun; Zhao, Lanxue; Qiu, Yu; Chen, Hongzhuan; Hu, Jiangmiao; Xu, Jianrong (Frontiers in Chemistry, 2022)
Background: A series of α-Mangostin (α-M) derivatives were designed and synthesized. α-M and four analogues were evaluated for their multifunctional anti-Alzheimer’s disease (anti-AD) effects on fibrillogenesis, microglial uptake, microglial degradation, and anti-neurotoxicity of Aβ, as well as LPS-induced neuroinflammation. The differences in bioactivities were analyzed to understand the structure-activity relationship for further modifications. Purpose: This study aims to investigate the anti-AD effects of α-M and elucidate its structure-activity relationship by comparing difference between α-M and several analogues. Methods: Aβ fibrillogenesis was detected by Thioflavin T fluorometric assay. The levels of Aβ1-42 and inflammatory cytokines were evaluated by enzyme-linked immunosorbent assay. Neuron viability was examined by the CCK-8 assay. The morphology of ZO-1 of bEnd.3 cultured in BV-2-conditioned medium was evaluated by immunofluorescence staining. Results: Aβ fibrillogenesis was significantly inhibited by co-incubation with α-M, Zcbd-2 or Zcbd-3. α-M, Zcbd-2, Zcbd-3 and Zcbd-4 decreased the levels of Aβ1-42 and inflammatory cytokines, and promoted Aβ uptake, degradation and anti-inflammation effects inflammation in microglia. α-M and Zcbd-3 protected neuron viability from Aβ-induced neurotoxicity, and preserved tight junction integrity of bEnd.3 against LPS-induced neuroinflammation. Conclusion: Zcbd-3 acted as α-M almost in all effects. The structure-activity analysis indicated that the 3-methyl-2-butenyl group at C-8 is essential for the bioactivity of α-M, while modifying the double hydroxylation at the C-2 position may improve the multifunctional anti-AD effects.